Amphotericin B resistance correlates with increased fitness in vitro and in vivo in Leishmania (Mundinia) martiniquensis - Mano, Chonlada; Kongkaew, Aphisek; Tippawangkosol, Pongsri; Somboon, Pradya; Roytrakul, Sittiruk; Pescher, Pascale; Späth, Gerald F.; Uthaipibull, Chairat; Tantiworawit, Adisak; Siriyasatien, Padet; Jariyapan, Narissara (Frontiers in Microbiology, 2023)
Amphotericin B (AmpB) deoxycholate is the available first-line drug used to treat visceral leishmaniasis caused by Leishmania (Mundinia) martiniquensis, however, some cases of AmpB treatment failure have been reported in Thailand. Resistance to drugs is known to affect parasite fitness with a potential impact on parasite transmission but still little is known about the effect of resistance to drugs on L. martiniquensis. Here we aimed to gain insight into the fitness changes occurring after treatment failure or in vitro-induced resistance to AmpB. L. martiniquensis parasites isolated from a patient before (LSCM1) and after relapse (LSCM1-6) were compared for in vitro and in vivo fitness changes together with an in vitro induced AmpB-resistant parasite generated from LSCM1 parasites (AmpBRP2i). Results revealed increased metacyclogenesis of the AmpBPR2i and LSCM1-6 strains (AmpB-resistant strains) compared to the LSCM1 strain and increased fitness with respect to growth and infectivity. The LSCM1-6 and AmpBRP2i strains were present in mice for longer periods compared to the LSCM1 strain, but no clinical signs of the disease were observed. These results suggest that the AmpB-resistant parasites could be more efficiently transmitted to humans and maintained in asymptomatic hosts longer than the susceptible strain. The asymptomatic hosts therefore may represent “reservoirs” for the resistant parasites enhancing transmission. The results in this study advocate an urgent need to search and monitor for AmpB-resistant L. martiniquensis in patients with relapsing leishmaniasis and in asymptomatic patients, especially, in HIV/Leishmania coinfected patients.